Edukacja konfucjańska w Chinach w okresie cesarskim – narzędzie wdrażania utopii autorytarnej? - Zemanek, Bogdan (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2022)
Chinese imperial examination system which evolved into its final form during the Song dynasty, created a social elite, uniformly educated according to Confucian precepts. This system aimed at preparing and recruiting properly morally qualified people who could be entrusted with governing the state, and especially– with managing the populus, morally short-sighted and focused on fulfilling its basic needs. State and private educational institutions inoculated the students with moral teachings, distilled from the examples from the past, regarded as the „golden age” of wise sage-kings and naturally harmonious society. These teachings underscored the importance of strict social hierarchy, obedience to the elder, wiser and of higher social standing in the said hierarchy in which social mobility was possible only through education and examinations. The society organized in this way was to fulfil everybody’s needs and diffuse tensions which could lead to conflicts and wars. This idea of a social system can be qualified as a conservative-utopian project because it postulates that wars and fighting, historically inherent parts of human condition, can be eliminated by educating people into obedient beings, calmly fulfilling their social roles prescribed by the wiser elites.
Keywords: Confucian education; Confucian morality; imperial examinations; conservative utopia; imperial China